Democratising the interface research-policymaking in landscape planning: experiences in Friuli Venezia Giulia (Italy) - Enrico Michelutti (Boletín de la Asociación de Geógrafos Españoles)
In the current, extended socio-environmental crisis, the interface research-policymaking in landscape planning has evolved, seeking responses to pressing global dynamics (e.g., climate change, international migration fluxes, etc.) and critical local demands (e.g., recognition of community-based initiatives, “public governance” of landscape interventions, etc.). Depending on contextual conditions, different political agendas and legal frameworks shape the interplay between knowledge production mechanisms and practices on landscape. The evolution of the interface research-policymaking involves the interactions between structured research policies and informal knowledge generation processes, the (ideological) use of participation in the actions on landscape and the redefinition of power equilibria in the planning arena. Exploring the experiences of landscape planning developed in Friuli Venezia Giulia, Italy (i.e., territorial plans involving landscape conservation norms, regional landscape plans, “integrated landscape projects”), the research shows the need to readdress landscape governance and policymaking towards inclusiveness, fostering knowledge co-production initiatives at all levels and (re-)thinking power as a complex factor of change in the relationships between planning authorities, academia, communities and citizens.